A policy on the move? Spatial planning and State Actors in the post‐devolutionary UK and Ireland. Issue 1 (13th January 2014) - Clifford, Ben; Morphet, Janice
<x xml:space="preserve">Abstract</x> Devolution has led to a dramatic restructuring of the UK state over the last 15 years. Planning is a devolved function and a concerted process of 'planning reform' has been implemented by devolved (and central) government since devolution, including a move from 'land‐use' to 'spatial planning'. Despite some expectations of, and pressure for, policy divergence post devolution, we draw on findings of discourse analysis to demonstrate how there are common framings and understandings of the concept of 'spatial planning' present in the policy documents of all the UK administrations, and in Ireland. As such, we conceptualise spatial planning as what, after Peck and Theodore (2010, Geoforum 41 169–74), we might consider a 'policy on the move'. Policy mobility is a fundamentally geographical phenomenon and its presence here raises questions about the mechanisms by which spatial planning has been mobilised. Drawing on interview data, we highlight the role of civil servants who meet through the British–Irish Council's workstream on spatial planning and a forum known as the 'Five Administrations' meetings. The relational connections between these state actors suggest that they are key 'transfer agents' and their role helps explain some of the path dependency in planning reform post devolution.